Improving Long-Pass Performance in Youth Football Players Through the BLAST Training Model - Fahrizqi, Eko Bagus; Rihatno, Taufik; Pelana, Ramdan (Physical Education Theory and Methodology, 2026)
Background. The long-pass kicking technique is a fundamental skill in football that can significantly influence match dynamics and contribute to team success. However, this technique remains a major challenge for youth football athletes, as it is often insufficiently emphasized in training programs. Therefore, an effective and structured training model is needed to improve long-pass performance. Objectives. This study aimed to examine the effectiveness of the BLAST training model in improving long-pass kicking technique among youth football athletes. Materials and Methods. This study employed a quasi-experimental design with a pretest–posttest control group approach. A total of 50 participants were divided into an experimental group (n = 25), which received the BLAST training model, and a control group (n = 25), which underwent conventional training provided by their coaches. The Rumi long-pass test was administered during both the pre-test and post-test to assess performance. Data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, Levene’s test of homogeneity, ANCOVA, independent samples t-tests, and N-gain score analysis. Results. The findings revealed that both groups showed improvements in long-pass kicking performance after the intervention. However, the experimental group demonstrated significantly greater improvement than the control group (p < 0.05). The experimental group achieved an average N-gain score of 62.56% (moderately effective), whereas the control group reached only 22.99% (low effectiveness). Conclusions. The results indicate that the BLAST training model is more effective than conventional training methods in improving long-pass kicking technique among youth football athletes.